2009
DOI: 10.4067/s0718-58392009000200011
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Dairy Farm Technical Efficiency Using Meta-Regression: An International Perspective

Abstract: This paper develops a meta-regression analysis to explain the variation of mean technical efficiency (PETP) measurements from a total of 65 frontier studies that report technical efficiency (ET) measurements at the dairy farm level in the literature published in English and Spanish. The analysis includes the effect of methodology on ET measurements, as well as the effect of the econometric procedure on the meta-regression estimates. Eight models were estimated, and two of these were selected: a fixed effects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…Putting the estimated efficiency scores for the 4 groups in context with the rich literature on dairy farm efficiency, we found the class-average scores to be relatively high [see Bravo-Ureta et al (2007) and Moreira López and Bravo-Ureta (2009)]. We attributed this finding mainly to the methodological design of the study, which mitigated the confusion of technological heterogeneity with technical inefficiency (see also Alvarez and del Corral, 2010).…”
Section: Technical Efficiencymentioning
confidence: 78%
“…Putting the estimated efficiency scores for the 4 groups in context with the rich literature on dairy farm efficiency, we found the class-average scores to be relatively high [see Bravo-Ureta et al (2007) and Moreira López and Bravo-Ureta (2009)]. We attributed this finding mainly to the methodological design of the study, which mitigated the confusion of technological heterogeneity with technical inefficiency (see also Alvarez and del Corral, 2010).…”
Section: Technical Efficiencymentioning
confidence: 78%
“…As reported by Olesen et al (1996), the effect of estimation methods are still controversial, an issue confirmed by the results reported by Rivas (2003), Moreira López (2006), Bravo-Ureta et al (2007) and Moreira López and Bravo-Ureta (2009). Thus, the following hypotheses are put forward:…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 83%
“…The studies of Rivas (2003), Moreira López (2006), Bravo-Ureta et al (2007) and Moreira López and Bravo-Ureta (2009) examine the effects of methodology on reported TE measures.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Table 7 Despite the large number of frontier models developed to improve measures of TE, there is no agreement as to the most appropriate methodology (Olesen, et al, 1996). The studies of (Rivas, 2003;Moreira López, 2006;Bravo-Ureta, et al, 2007;Moreira López & Bravo-Ureta, 2009) examine the effects of methodology on reported TE measures.…”
Section: Data Description and Hypothesismentioning
confidence: 99%
“…Meta-analysis is an approach that uses published empirical estimates of some indicator and attempts to explain the variation of these estimates based on differences cross studies (Stanley & Jarrell, 1989). The procedures employed in meta-analysis permit quantitative reviews and syntheses of studies examining similar research issues (Rivas, 2003;Moreira López, 2006;Bravo-Ureta, et al, 2007;Moreira López & Bravo-Ureta, 2009 Model I:…”
Section: Meta-regression Analysismentioning
confidence: 99%